Environmental variation is a major predictor of global trait turnover in mammals. (18th October 2017) - Holt, Ben G.; Costa, Gabriel C.; Penone, Caterina; Lessard, Jean‐Philippe; Brooks, Thomas M.; Davidson, Ana D.; Blair Hedges, S.; Radeloff, Volker C.; Rahbek, Carsten; Rondinini, Carlo; Graham, Catherine H.
Abstract: Aim: To evaluate how environment and evolutionary history interact to influence global patterns of mammal trait diversity (a combination of 14 morphological and life‐history traits). Location: The global terrestrial environment. Taxon: Terrestrial mammals. Methods: We calculated patterns of spatial turnover for mammalian traits and phylogenetic lineages using the mean nearest taxon distance. We then used a variance partitioning approach to establish the relative contribution of trait conservatism, ecological adaptation and clade specific ecological preferences on global trait turnover. Results: We provide a global scale analysis of trait turnover across mammalian terrestrial assemblages, which demonstrates that phylogenetic turnover by itself does not predict trait turnover better than random expectations. Conversely, trait turnover is consistently more strongly associated with environmental variation than predicted by our null models. The influence of clade‐specific ecological preferences, reflected by the shared component of phylogenetic turnover and environmental variation, was considerably higher than expectations. Although global patterns of trait turnover are dependent on the trait under consideration, there is a consistent association between trait turnover and environmental predictive variables, regardless of the trait considered. Main conclusions: Our results suggest that changes in phylogenetic composition are not always coupled with changes in trait composition on a global scale and that environmental conditions are strongly associated with patterns of trait composition across species assemblages, both within and across phylogenetic clades.